Effectiveness of Rose and Jasmine Aromatherapy on The Phase 1 Labor Duration in Intrapartum Mothers at Aisyiyah General Hospital, Kudus, Central Java - Asmawati, Lilik; Fatmasari, Diyah; Suwondo, Ari; Widyawati, Melyana Nurul (Journal of Maternal and Child Health, 2024)
Background: Unhandled prolonged labor can cause death for the mother and baby. Prolonged labor is caused by inadequate contraction. Uterotonics and aromatherapy can improve the contraction. Rose and jasmine aromatherapy increase oxytocin level and aid the birth process. This study aims to compare the effectiveness of rose and jasmine aromatherapy on duration of labor in women in the first stage of labor at Aisyiyah Hospital Kudus. Subject and Methods: This research was a true experimental study with posttest-only control group design. The number of samples was determined using simple random sampling. The number of samples was 45 respondents (15 rose aromatherapy, 15 jasmine aromatherapy, 15 control). Aromatherapy (1-3%) was given through diffuser for 30 minutes. Each respondent who had prolonged labor was given aromatherapy during first stage of labor, then the duration of labor was measured. The data was analyzed using Kruskal-Wallis test. Results: In the normality test by Shapiro-Wilk test, the value of p=0.006 (p<0.05), which means that the data is not normally distributed. Homogeneity test with the Lavene test yields p=0.044 (p<0.05) which indicates that the variance of data is not homogeneous. Then continued with the Kruskal-Walls test, it was found that there was no significant difference in the effectiveness of giving rose aromatherapy, jasmine aromatherapy and standard treatment on the duration of labor in women with prolonged labor (p=0.104). Conclusion: There was no significant difference in the labor duration in rose, jasmine and control groups.